Charged particles: Unique tools to study irradiation resistance of concentrated solid solution alloys. (20th March 2023) - Zhang, Yanwen; Wang, Lumin; Weber, William J.
Graphical abstract: Image, graphical abstract Abstract: Many multicomponent concentrated solid solution alloys (CSAs), including high-entropy alloys (HEAs), exhibit improved radiation resistance and enhanced structural stability in harsh environments. To study and assess irradiation resistance of nuclear materials, energetic ion and electron beams are commonly used to create displacement damage. Moreover, charged particles of ions, electrons, and positrons are unique tools to create and characterize radiation effects. Ion beam analysis (e.g., Rutherford backscattering spectrometry, nuclear reaction analysis, and time-of-flight elastic recoil detection analysis), electron microscopy techniques (e.g., transmission or scanning electron microscopy, and electron diffraction), and positron annihilation spectroscopy have been applied to characterize irradiated CSAs or HEAs to understand defect formation and evolution together with chemical and microstructural information. Their distinctive analyzing power and some perspectives in these techniques are reviewed. In developing structural alloys desirable for applications in advanced reactors, neutron exposure is a critical test but the limitation in achievable high damage levels is, however, a bottleneck. Ion irradiation is often used as a surrogate for neutron irradiation, and the associated reduced transmutations and higher displacements per atom (dpa) rates are desirable for materials research. Nevertheless, cautions need to be taken when relying on ion irradiation results for reactor evaluations. Literature on differences between ions and neutrons is briefly reviewed. In addition, the links to bridge the current advances on fundamental understandings to reactor applications are discussed to lay the groundwork between neutrons and ions for radiation effects studies.